Out of and into authoritarian law - Sajó, András (Kluwer Law International, 2003)
The essays in this collection reflect on the promises, hopes and fears dominant in the narratives on and realities of doing away with authoritarian regimes. They combine first-hand insider accounts with interdisciplinary scholarly analysis.